Pemberdayaan Perekonomian Masyarakat dengan Pemanfaatan Buah Kelapa Menjadi Olahan Makanan Lepa di Desa Merbaun, Kecamatan Amarasi Barat - Dedy Raidons; Helda Marlin (Institut Nalanda, 2024)
This Community Service Program aims to empower the economy of the Merbaun Village community, Amarasi Barat District, through the utilization of coconut as an ingredient for the food product